Effects of Cu substitution on microstructures and microwave dielectric properties of Li2ZnSiO4 ceramics - Zhang Qin; Su Hua; Tang Xiaoli (MATEC Web of Conferences, 2022)
Herein, the influence of Cu2+ substitution on the phase composition, bulk density, microstructures, and microwave dielectric properties of Li2CuxZn1−xSiO4 (0 ≤ x ≤ 0.06) ceramics prepared by a solid-state reaction were investigated. The results of XRD and mapping showed that Cu2+ substitution can avoid the influence of secondary phase on the properties of samples. According to the analysis of bulk density, microstructure and microwave dielectric properties, a proper amount of Cu substitution not only improved the sintering characteristics of Li2CuxZn1−xSiO4 ceramics, reduced the densification temperature from 1250 °C to 950 °C, but also increased the Q×f value. Furthermore, Cu2+ substitution also improved the temperature stability of the samples. Particularly, the Li2Cu0.04Zn0.96SiO4 ceramics sintered at 950 °C for 5 h possessed excellent microwave dielectric properties: εr = 5.624, Q×f = 12,764 GHz, and τf = −77 ppm/°C, exhibiting a potential for the low temperature co-fired ceramic applications.